OPENNES AND TRANSPARENCY OF STATE AND LOCAL BUDGETS IN UKRAINE - J. Nakonechna; L. Demydenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
This article is devoted the method of calculating the Open Budget Index, which established by the international organization "International Budget Partnership". This article reveals the procedure of disclosure of budget documents that affects the ranking of countries within the open budget index. Determined are the Directions for improved index transparency of public finance in Ukraine. Described as well is the first results of the electronic public procurement system "Prozorro".